Design of Mobile Web-Based Learning Media - Rony Kusmaladi; Ahmad Fauzi; Muhammad Saleh; Nurul Ahyana (Jurnal Indonesia Sosial Sains, 2026)
The rapid advancement of digital technology has transformed educational practices, demanding innovative and accessible learning solutions, particularly in vocational maritime education. This study aims to design, validate, and evaluate the effectiveness of mobile web-based learning media for Maritime English subjects at Barombong Shipping Polytechnic. The development followed the ADDIE model (Analyze, Design, Develop, Implement, Evaluate), utilizing Glide Apps as the primary platform and Google Sheets as the backend database. Data were collected through questionnaires distributed to 28 cadets and 8 lecturers, measuring aspects of effectiveness, practicality, validity, and learning motivation using a 4-point Likert scale. The results showed that the learning media achieved an overall effectiveness score of 89.5% from cadets, with an average score of 3.58 out of 4.0, categorized as very effective. Lecturers' validity assessments indicated that the media met validity criteria, particularly in cross-platform compatibility, which scored the highest at 4.0. Practicality evaluations revealed that 8 out of 10 indicators fell into the highly valid category, especially in ease of access, navigation, and user satisfaction. The study concludes that the mobile web-based learning media is valid, practical, and effective in supporting English learning. However, aspects such as learning independence, focus, and speaking skill encouragement require further improvement. A blended learning approach combining digital media with direct teacher interaction is recommended to optimize learning outcomes.